The Interactive Effect of Pruning Level and Irrigation Strategy on Water Use Efficiency of Vitis vinifera L. cv. Shiraz - Bindon, K.A.; Dry, P.R.; Loveys, B.R. (South African Journal of Enology and Viticulture, 2016)
A partial rootzone drying (PRD) irrigation technique (0.5 ML/ha) was compared with a standard irrigation treatment (1 ML/ha) at three different pruning levels of 30, 60 and 120 nodes per grapevine in Vitis vinifera L. cv Shiraz. The PRD irrigation technique was applied to a single side of the grapevine rootzone at a time, 45 cm from the trunk, and the sides were switched in 10-day cycles. For the standard irrigation treatment, both sides of the grapevine were irrigated. At the end of an irrigation cycle, the PRD treatment resulted in reduced midday readings of stomatal conductance and stem (ψS) and leaf (ψL) water potential relative to the control treatment. During the switch between irrigation cycles, when the soil water profile of both the ‘wet’ and ‘dry’ sides of the PRD-treated grapevines was refilled, stomatal conductance, ψS and ψL were restored to the same levels as for the control experiment. As node number per grapevine increased, berry size and winter pruning weight were reduced and yield increased. In the first season of the experiment, the PRD treatment did not have a significant effect on berry size, yield and pruning weight, although shoot length was reduced in response to PRD for all the pruning treatments. In a subsequent season, PRD was found to reduce yield, primarily through a reduction in berry set. Water use efficiency measured as t/ML irrigation water applied was increased significantly as crop load increased, and was enhanced in response to the PRD irrigation technique.